Tail gait - Brown, Rita Mae; Brown, Sneaky Pie, 1982-; Gellatly, Michael (New York : Bantam, 2015)
"There's nothing like a tail well-told. Rita Mae Brown and her feline co-author Sneaky Pie Brown return with an all-new mystery featuring Mary Minor "Harry" Haristeen, crime-solving cats Mrs. Murphy and Pewter, and ever-faithful Tee Tucker the corgi"--
"In the twenty-third book in the New York Times bestselling mystery series, Rita Mae Brown and her feline co-author Sneaky Pie Brown return with an all-new mystery starring Mary Minor "Harry" Haristeen, intrepid kitty sleuths Mrs. Murphy and Pewter, and Tee Tucker, the ever-faithful crime-solving corgi"--
Library Journal Prepub Alert
Keywords: Murphy, Mrs. (Fictitious character) -- Fiction; Haristeen, Harry (Fictitious character) -- Fiction; Women detectives -- Virginia -- Fiction; Women cat owners -- Fiction; Cats -- Fiction; Mystery fiction